The impact of gender and age on bullying role, self-harm and suicide: Evidence from a cohort study of Australian children - Ahmad, Kabir; Beatson, Amanda; Campbell, Marilyn; Hashmi, Rubayyat; Keating, Byron W; Mulcahy, Rory; Riedel, Aimee; Wang, Shasha (My University, 2023)
There has been limited longitudinal investigation to date into the association between bullying, self-harm, and suicidality in Australia and the impact of specific demographic differences on this relationship. This is despite the continued rise in the incidence of bullying, self-harm, and suicide. As such, the current study draws on data from the Longitudinal Survey of Australian children (LSAC) to examine the association between bullying, self-harm, and suicidality and explore the impact of demographic differences across three bullying related behaviors (being bullied, bullying others and being both bullied and bullying others). The evidence indicates that bully-victims exhibit the highest risk of self-harm and suicidality in Australia. When considering demographic differences, it was identified that females and adolescents aged 16-17-years-of-age had the highest risk of self-harm and suicidality. Further, a direct curvilinear relationship between age and the categories of self-harm was identified with an inflection point around 16-17 years. The study supports the need for further investigation into the association between bullying, self-harm, and suicidality longitudinally with a particular focus on other moderators.
PLOS ONE
Keywords: Disadvantage, adversity and resilience; Health and wellbeing